Analisis Pengaruh Fundamental Makro Ekonomi Terhadap Pergerakan Indeks Harga Saham Gabungan di Bursa Efek Indonesia - Muhammad Ashary Anshar; Muh. Jabir (Jurnal Pasar Modal dan Bisnis, 2021)
This study aims to analyze and determine the effect of inflation, exchange rates, and the Dow Jones index on the movement of the composite stock price index on the Indonesian stock exchange. The analysis method used in this research is multiple linear regression analysis, partial test (t test), determination coefficient test, and classical assumption test which consists of normality test, heteroscedasticity test, autocorrelation test and multicolonierity test with the help of SPSS statistic 24 for windows. The sample in this study is monthly data on inflation, exchange rates and the Dow Jones index with the observation period being 4 (four) years from 2016 - 2019. The results of this study indicate that inflation has a negative and insignificant effect on the movement of the composite stock price index on the Indonesian stock exchange, the exchange rate has a negative and significant effect on the movement of the composite stock price index on the Indonesian stock exchange, and the Dow Jones index has a positive and significant effect on the movement. composite stock price index on the Indonesian stock exchange.